Handbook of research on interdisciplinary approaches to decision making for sustainable supply chains - Awasthi, Anjali, 1976-; Grzybowska, Katarzyna, 1974- (Advances in logistics, operations, and management science (ALOMS) book series., 2020)
"This book examines interdisciplinary approaches to sustainable supply chain management. It also explores methods, tools, and techniques for sustainable supply chain planning"--